Inventing and Reinventing the Goddess: Contemporary Iterations of Hindu Deities on the Move - Sree Padma (Lexington Books, 2014)
The volume investigates two related processes: First, it underscores the manner in which the religious cultures of goddesses are reflexes of larger social processes occurring historically in local contexts. Second, it illustrates transformations in how these same goddesses are understood when they migrate from indigenous social and cultural contexts to destinations with their devotees.